The Effect of Strengthening Islamic Character Education, a Culture of Discipline, and Digital Literacy on Students’ Social Responsibility: A Quantitative Analysis of Vocational High School Students in the Digital Era - Fiki Sanjaya; Muhammad Ilmiawan; Gholib Amar Ahsan; Azzam Taufiqy; Muhammad Alfi Syahrin (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This study aims to analyse the influence of strengthening Islamic character education, disciplinary culture, and digital literacy on students' social responsibility at the Vocational High School (SMK) level in the digital era. The rapid development of information technology has brought significant changes to students' patterns of social interaction, thereby creating new challenges in shaping socially responsible character. This study employed a quantitative approach with an explanatory survey design. The population consisted of all vocational high school students, with the sample determined using proportional random sampling techniques. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression to determine the partial and simultaneous effects among variables. The results showed that strengthening Islamic character education had a positive and significant effect on students' social responsibility, disciplinary culture also made a significant contribution, and digital literacy strengthened the relationship between Islamic character and students' social behaviour. Simultaneously, the three variables had a significant influence on students' social responsibility. This study contributes to the development of Islamic Religious Education studies based on character education in the digital era and provides practical implications for schools in designing character-building strategies that are relevant to contemporary challenges